Study of the Influence of the Technological Regime of the Production of Water Extraction from Rosehip Fruits (Rosae fructus) on the Content of Ascorbic Acid - F. V. Sobin; L. K. Korosteleva; T. A. Lutkova; N. V. Dozmorova (Разработка и регистрация лекарственных средств)
Introduction. COVID-19 is recognized as the most significant pandemic of the modern era. Studies have shown the potential benefits of taking ascorbic acid in the complex treatment of this disease, especially in people with vitamin C deficiency. One of the most popular and affordable sources of ascorbic acid in the diet are rosehip fruits. The quality of water extracts from plant raw materials depends on a number of technological factors. The study of the influence of the technological regime of the production of water extraction from rosehip fruits on the release of ascorbic acid in the obtained dosage forms is relevant.Aim. To obtain water extracts from rosehip fruits by various production modes and to study the effect of technological parameters on the content of ascorbic acid.Materials and methods. The object of the study was rosehip fruits in bundles and water extracts based on them, obtained in the 6 different ways. Pharmacopoeial techniques, manufacturers' recommendations, as well as thermos infusion with and without preheating of the thermos flask were used. For quantitative determination of the ascorbic acid in the obtained aqueous extracts, we used the pharmacopoeia method (titration with 2,6-dichlorophenolindophenolate sodium).Results and discussion. The lowest content of ascorbic acid was noted in the decoction according to the pharmacopoeia method. High levels of ascorbic acid content were noted in the variants of thermos infusion of rosehip fruits.Conclusion. We have obtained extemporal water extracts of rosehip fruits by the 6 different extraction modes. According to the content of ascorbic acid, the most effective method of obtaining extemporal water extraction of rosehip fruits is a six-hour thermos infusion with preheating of the thermos flask. The largest amount of ascorbic acid is released during a six-hour thermos infusion. In the twelve-hour thermos infusions, a decrease in the amount of ascorbic acid was found. It was found that preheating the thermos flask leads to an increase in the yield of ascorbic acid in aqueous extraction by 25 %.